2017
DOI: 10.5530/ijper.51.3s.77
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Methyl Jasmonate on Growth and Caffeic Acid Derivative Contents of In vitro Shoot and Roots in Echinaceae (Echinacea Purpurea)

Abstract: This study was carried out to determine the effects of methyl jasmonate (MeJA) applications on growth and accumulation of caffeic acid derivatives (CADs) in shoots and roots grown in vitro. For this aim, 28 days old plants obtained from seeds were cultured in ½ Murashige and Skoog media containing different concentrations of MeJA (0, 10, 50 and 100 μM) and plants were harvested in three times at 15 days intervals. After harvest, growth parameters and CADs in shoot and roots were determined, separately. All gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…26 The previous studies reported similar results as the present study in that elicitation with MeJa significantly enhanced TPC and TFC in hairy root cultures of other plants. 11,27,28 Elicitation also enhanced the accumulation of hydroxycinnamic acids; particularly, MeJa significantly enhanced chicoric acid accumulation in L. indica L. Similar results were reported for Echinacea purpurea 29 and Echinacea angustifolia. 30 Furthermore, secondary metabolites were reportedly enhanced by increasing exposure duration in hairy root cultures of Salvia miltiorrhiza , 31 Salvia virgata Jacq., 27 and Rubia tinctorum .…”
supporting
confidence: 79%
“…26 The previous studies reported similar results as the present study in that elicitation with MeJa significantly enhanced TPC and TFC in hairy root cultures of other plants. 11,27,28 Elicitation also enhanced the accumulation of hydroxycinnamic acids; particularly, MeJa significantly enhanced chicoric acid accumulation in L. indica L. Similar results were reported for Echinacea purpurea 29 and Echinacea angustifolia. 30 Furthermore, secondary metabolites were reportedly enhanced by increasing exposure duration in hairy root cultures of Salvia miltiorrhiza , 31 Salvia virgata Jacq., 27 and Rubia tinctorum .…”
supporting
confidence: 79%
“…In addition, a suitable gene marker C 3 H, p-coumarate-3-hydroxylase, useful for early predictions of the cell's aptitude to synthesize these molecules, has been identified [100]. MeJA treatments raised the caffeic acid derivatives (CADs) in both shoots and roots in E. purpurea applied with 100 µM MeJA and collected 45 days after application, but other growth parameters of the shoot and roots declined in line with the rising level of MeJA treatments [101]. Cui et al [102] reported that MeJA treatment (100 µM) in a 500 L pilot-scale bioreactor culture system in adventitious roots of E. angustifolia generated 12.3 mg/g DW echinacoside.…”
Section: Salinitymentioning
confidence: 99%